Relationship between Diet and Medication Adherence to the Blood Pressure of Hypertensive Elderly in East Sumba - Waluwanja, Relithen Umbu; Putri, Ronasari Mahaji; Devi, Hilda Mazarina (Jurnal Surya, 2022)
Introduction: The incidence of hypertension in the elderly is increasing due to changes in people's lifestyles globally, low awareness to regulate diet, and low adherence to taking medications. This study aims to determine the relationship between hypertension-inducing diet and adherence to taking medications with the blood pressure of hypertensive elderly at the Wangga Pakuki Elderly Posyandu, Wangga Village, Kambera District, East Sumba.Methods: the variables of this study is hypertension-inducing diet and adherence to taking medications with the blood pressure of hypertensive elderly at the Wangga Pakuki Elderly Posyandu, Wangga Village, Kambera District, East Sumba. Primary data sources and data collection using dietary questionnaire sheets and medication adherence, as well as blood pressure observation sheets.Results: Most of the hypertensive elderly in the elderly posyandu had a hypertension- inducing diet in the high category (52%), almost half of the elderly had low medication adherence (35.8%) and had stage 3 hypertension (40.3%), and there was a relationship between hypertension-inducing diet (p=0.001) (OR=6.5) and adherence to taking medications (p=0.006) (OR=4.3) with the blood pressure of hypertensive elderly.Conclusion: There is a relationship between diet and adherence to taking medications to the blood pressure of the elderly with hypertension. Maintaining a regular diet and taking medications is highly recommended to maintain blood pressure, in addition to doing light walking activities, regular blood pressure checks and stress management.